2016
DOI: 10.1093/cid/ciw036
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Xpert MTB/RIF and Alternative Specimen Collection Methods for the Diagnosis of Tuberculosis in HIV-Infected Children

Abstract: The ANRS (Agence Nationale de Recherche sur le Sida) 12229 PAANTHER (Pediatric Asian African Network for Tuberculosis and HIV Research) 01 study is registered at ClinicalTrials.gov (NCT01331811).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 28 publications
4
83
1
2
Order By: Relevance
“…It showed lower sensitivity and specificity (69.7% and 94.0%, respectively) as compared with sputum cultures. The obtained results were lower than other studies [17, 18, 40, 43, 44]. Inhibitors were likely to be the cause of most false-negative fecal PCR results in our study.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…It showed lower sensitivity and specificity (69.7% and 94.0%, respectively) as compared with sputum cultures. The obtained results were lower than other studies [17, 18, 40, 43, 44]. Inhibitors were likely to be the cause of most false-negative fecal PCR results in our study.…”
Section: Discussioncontrasting
confidence: 87%
“…tuberculosis in samples that can be obtained more easily. Stool holds promise for PTB diagnosis in patients who are unable to produce sputum and potentially avoid more invasive procedures [16, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Two pilot studies from South Africa (29, 34) and a multicentre study of Asian and African HIV-infected children with suspected intrathoracic TB (35) reported sensitivities of 41-75%, with specificities >97.5% for stool Xpert vs. culture of respiratory samples. The higher sensitivity reported compared to our results can be explained by the severe spectrum of TB in children with Xpert-positive stool included in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the test failed to identify 32% of TB cases, it may be of more value in HIV-infected children, who run a high risk of acquiring TB, as well as high risk of disease progression. Marcy et al reported a sensitivity of 62% for stool Xpert testing among HIV-infected children 19. Smear microscopy, the routinely available test at primary care centres, has a sensitivity of <10–15% in children with proven TB,20–22 and its performance is even poorer in those with HIV infection 23…”
Section: Discussionmentioning
confidence: 99%